Longitudinal changes of anxiety and depressive symptoms during the COVID-19 pandemic in Germany: The role of pre-existing anxiety, depressive, and other mental disorders. (April 2021) - Bendau, Antonia; Kunas, Stefanie Lydia; Wyka, Sarah; Petzold, Moritz Bruno; Plag, Jens; Asselmann, Eva; Ströhle, Andreas
Highlights: Multilevel analyses revealed changes in COVID-19-related fear, anxiety, and depressive symptoms. Symptoms were higher with vs. without anxiety, depressive and other mental disorders. All symptoms decreased on average across the first months of the pandemic. This decrease was stronger in individuals with vs. without anxiety disorders. A driving factor were initially high symptoms in generalized anxiety disorders. Abstract: Especially individuals with mental disorders might experience an escalation of psychopathological symptoms during the COVID-19 pandemic. Therefore, we investigated the role of anxiety, depressive, and other mental disorders for levels and longitudinal changes of COVID-19-related fear, anxiety and depressive symptoms during the first months of the COVID-19 pandemic in Germany. In a longitudinal observational design with four assessment waves from March, 27th until June, 15th 2020, a total of 6, 551 adults from Germany was assessed. 4, 175 individuals participated in one, 1, 070 in two, 803 in three, and 503 in all four waves of data collection. Multilevel analyses revealed that across all assessment waves, COVID-19-related fear, anxiety, and depressive symptoms were significantly higher in individuals with vs. without anxiety, depressive, and other mental disorders. All symptoms decreased on average over time, and this decrease was significantly stronger in individuals with vs. without anxiety disorders, and particularly driven by individuals with generalized anxiety disorder. Our findings suggest that individuals with mental disorders, especially anxiety disorders – and in particular those with a generalized anxiety disorder – seem to be vulnerable to experience psychological strain in the context of the pandemic, might likely overestimate potential threat, and should be targeted by preventive and therapeutic interventions.